2017
DOI: 10.1021/acs.chemmater.6b04706
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible Hybrid Polymer Aerogels and Xerogels Based on Resorcinol-Formaldehyde with Enhanced Elastic Stiffness and Recoverability: Insights into the Origin of Their Mechanical Properties

Abstract: Flexible low-density materials, such as aerogels and polymer foams, have received increasing attention as energy absorbers and cushions that protect artificial products and human bodies. Microscopic geometry is a crucial factor determining their mechanical functions, i.e. strength and toughness (flexibility). However, it is a formidable challenge to combine these two properties because they are mutually elusive in general; stiff materials are brittle, while flexible ones are soft. Here, we demonstrate lightwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 59 publications
4
74
0
Order By: Relevance
“…( B ) Relative strength and modulus as functions of the relative density of CPF woods. ( C ) Ashby chart plotting compressive yield strength versus density for polymeric woods and other engineered materials, including cast resin ( 14 ), SiC foam ( 15 ), 3D-printed honeycomb ( 14 ), mullite-ZrO 2 foam ( 16 ), PF carbon foam ( 24 ), and RF aerogel ( 25 ). Symbols ‖ and ⊥ represent the compressive directions that are parallel and perpendicular to the channels, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( B ) Relative strength and modulus as functions of the relative density of CPF woods. ( C ) Ashby chart plotting compressive yield strength versus density for polymeric woods and other engineered materials, including cast resin ( 14 ), SiC foam ( 15 ), 3D-printed honeycomb ( 14 ), mullite-ZrO 2 foam ( 16 ), PF carbon foam ( 24 ), and RF aerogel ( 25 ). Symbols ‖ and ⊥ represent the compressive directions that are parallel and perpendicular to the channels, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The elastic moduli of the polymeric woods are much higher than those of corks and the isotropous phenolic aerogels (fig. S17) ( 24 , 25 ). The elastic moduli are comparable to those of the cellular ceramic materials but are lower than those of natural woods.…”
Section: Resultsmentioning
confidence: 99%
“…However,t raditional aerogels are usually dried via costly supercritical drying (SCD) and exhibit low mechanical strength because of their intrinsically fragile/brittle networks,w hich need to be addressed before their practical applications.To overcome the costly drying process and brittleness, many efforts have been made to lower the cost by ambient pressure drying (APD), [23] freeze drying (FD) [22] and vacuum drying (VD), [24] and reinforce the aerogels by av ariety of methods.C ross-linking of aerogels with organic polymers is aw idely used method to reinforce the aerogels but usually results in lower porosity and higher density that limit their applications. [25,26] Flexible polymer-based aerogels can be obtained from resorcinol-formaldehyde, [27] poly(vinyl alcohol), [28] and supramolecules, [29] and some of them exhibit good absorption of organic solvents/oils.A nother kind of aerogels based on biomass such as nanocellulose and chitosan with compressibility and bendability have been reported. [30,31] Owing to their highly porous nanostructure that is composed of nanofibers,t hey show excellent thermal insulation performances.B esides,a ssembly of nanofibers via as pecific method can give compressible and elastic cellular aerogels with high pressure-sensitivity and good absorption/separation properties.…”
mentioning
confidence: 99%
“…Recently, Hasegawa et al showed that if the TEG/HCl content in H 2 O is changed in the RF system, significantly altered morphologies of the carbon monoliths will be obtained. [66] In that regard, we used 2 M and 3 M HCl when increasing the Ti 4 + amount, instead of 1 M HCl, in order to overcome the volume ratio issue. This leads again to C/TiO 2 monoliths with hierarchical structure featuring a macroporous network comprising mesoporous struts (Figure 4 b, c and d).…”
Section: Influence Of the Ti Precursormentioning
confidence: 99%